Mitigating anxiety among indonesian students: The moderating role of islamic religiosity in social support effects - Fuad Nashori; Diana, Raden Rachmy; Rahmat Aziz; Harianti, Winda Sri; Alfian Fajar Budi Nugroho (Psikis : Jurnal Psikologi Islami, 2025)
Anxiety is a common mental health issue among university students, which significantly affects their academic performance and well-being. While social support is widely recognized as a protective factor against anxiety, its effectiveness may vary depending on individual psychological factors such as religiosity. This study aims to examine the moderating role of Islamic religiosity in the relationship between social support and anxiety among Indonesian university students. By investigating the interaction, the research seeks to provide insights into faith-based coping mechanisms that may enhance students’ psychological resilience. A cross-sectional survey was conducted among 523 university students in Indonesia using purposive sampling. Data were collected through an online questionnaire measuring anxiety (DASS-42), Islamic religiosity (MUDRAS), and social support (MSPSS). Moderation analysis was performed using Moderated Regression Analysis (MRA) Model 1. The findings indicated that both social support (Z = -3.09, p = .002) and Islamic religiosity are significantly associated with lower anxiety levels (Z = -3.52, p < .001). Furthermore, Islamic religiosity moderated the relationship between social support and anxiety, suggesting that students with higher religiosity experience greater psychological benefits from social support (Z = -2.39, p = .017). These results highlighted the importance of integrating religious and social support into student mental health programs. Universities should consider implementing faith-based support systems to enhance students' psychological resilience and well-being, particularly in religiously oriented communities